TPX2 enhances the transcription factor activation of PXR and enhances the resistance of hepatocellular carcinoma cells to antitumor drugs - Hongbo Wang; Fang Chu; Xiao-feng Zhang; Peng Zhang; Li-xin Li; Yun-long Zhuang; Xiao-feng Niu; Xi He; Zhi-jie Li; Ying Bai; Da Mao; Zhen-wen Liu; et al. (Cell Death and Disease, 2023)
Abstract The pregnane X receptor (PXR) is an important regulator of hepatocellular carcinoma cellular resistance to antitumor drugs. Activation of PXR was modulated by the co-regulators. The target protein for the Xenopus plus end-directed kinesin-like protein (Xklp2) known as TPX2 that was previously considered as a tubulin regulator, also functions as the regulator of some transcription factors and pro-oncogenes in human malignances. However, the actions of TPX2 on PXR and HCC cells are still unclear. In the present study, our results demonstrate that the high expression of endogenous mRNA level of TPX2 not only correlated with the poor prognosis of advanced HCC patients who received sorafenib treatment but also with expression of PXR’s downstream genes, cyp3a4 and/or mdr-1. Results from luciferase and real-time polymerase chain reaction (qPCR) showed that TPX2 leads to enhancement of the transcription factor activation of PXR. Protein–protein interactions between PXR and TPX2 were identified using co-immunoprecipitation. Mechanically, overexpression of TPX2 led to enhancement of PXR recruitment to its downstream gene cyp3a4’s promoter region (the PXRE region) or enhancer region (the XREM region). Treatment of HCC cells with paclitaxel, a microtubule promoter, led to enhancement of the effects of TPX2, whereas vincristine, a microtubule depolymerizing agent caused a decrease in TPX2-associated effects. TPX2 was found to cause acceleration of the metabolism or clearance of sorafenib, a typical tyrosine kinase inhibitor (TKI) in HCC cells and in turn led to the resistance to sorafenib by HCC cells. By establishing novel actions of TXP2 on PXR in HCC cells, the results indicate that TPX2 could be considered a promising therapeutic target to enhance HCC cells sensitivity to antitumor drugs.